Static tensile test with imperfect dimension - Chang, Gabriel Yew Chain (Nanyang Technological University, 2023)
This Final Year Project (FYP) is regarding the experimentation, comparison, and investigation of aluminium 6061-T6 mechanical properties with imperfect dimensions in both longitudinal direction and transverse directions, specifically an artificially drilled hole mimicking defects. Experiment is to conduct static tensile test to determine the mechanical properties of aluminium 6061-T6. Experiment test conditions will be explained and determined by literature review and results obtained by past year students. Test specimen and procedures will follow ASTM E8/E8M-16a strictly and guide provided by past year students. Mechanical properties will be extracted from a stress-strain curve plotted with the obtained experiment data. The objective of this report is to understand and compare how defects such as a hole affects the mechanical properties of aluminium 60610-T6 obtained, in both longitudinal and transverse directions. Author will seek to verify and prove the conclusion of past year students. It covers reasons as to why a hole imperfection was chosen and will also investigate the reliability of results and possible causes of deviation in results as compared to results achieved by previous students. Lastly, based on analysis and review, solutions will be recommended to help improve future experimentations for achieving accurate results.